Meta-Analysis: The Influence of Mathematical Digital Literacy on Mathematics Learning - Dewi, Rahmita Fitri; Sulistyowati, Fitria; Kusumaningrum, Betty; Septiani, Devi; Utami, Wikan Budi (Universitas Suryakancana, 2025)
The advancement of technology and information in the industrial revolution era has brought significant changes in education which demands strong digital literacy among students to face the challenges of the 21st century. Digital literacy not only includes the ability to read and understand information, but also integrates technology in the learning process and problem solving. This study uses a meta-analysis method to evaluate and combine the results of various studies on digital literacy in mathematics learning in Indonesia. The purposive sampling technique was used to select 12 relevant scientific articles from the last seven years taken from Google Scholar. Data were collected through documentation and filtered to ensure compliance with the research topic. Effect size analysis was used to measure the effect of digital literacy on mathematics learning. The characteristics of the studies analyzed in this study include the year of research, level of education, and type of publication. Statistically, it was obtained that the application of Digital Literacy to mathematical abilities was influenced by the level of education used. The integration of digital technology in mathematics learning at the high school level has a significant impact on improving student achievement. The results of the study indicate that the integration of digital technology prepares students for future challenges with increasingly advanced technology.